Pengaruh Dana Bagi Hasil (DBH) Dan Dana Desa Terhadap Pertumbuhan Ekonomi Dengan Belanja Modal Sebagai Variabel Moderasi Di Koridor Bali – Nusa Tenggara - Nova Rizkya Ning Putri; Ida Nuraini (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2023)
This study aims to determine the effect of profit-sharing funds and village funds with capital expenditure as a moderating variable in the Bali-Nusa Tenggara Corridor. The data used is secondary data obtained from BPS and the directorate general of financial balances using the panel data regression method using the random effects model and moderating regression analysis for the moderation test. The results of this study indicate that revenue sharing and village funds have a significant effect on economic growth in the Bali-Nusa Tenggara Corridor with capital expenditure acting as a moderating variable